Design and Implementation of a Solar-Powered Pest Repellent System for Shallot Farms Using Ultrasonic, and Light Emitters Based on ESP32 - Hutajulu, Albert Gifson; Daffa, Dhimas Alviero (Jurnal Teknik Informatika (Jutif), 2025)
Shallots are an agricultural commodity of high economic value that often experiences pest attacks, causing a decrease in crop yields. Commonly used pest control methods, such as pesticides and manual expulsions, are often less effective and can have a negative impact on the environment. Therefore, this research aims to design and develop a pest repellent based on the ESP32 microcontroller that can be operated in automatic or manual mode and utilize the resources of the Solar Power Plant (PLTS) supported by ultrasonic loads and LED lights. The research methods used include device design using PCB, load testing, and system performance analysis based on the voltage and current generated. The test results show that the system has high stability during the day with an average voltage of 12.54V and an average current of 0.07A for ultrasonic loads. However, at night, the system degrades, because the solar cells do not produce energy. The stability of the system is also more optimal at the use of ultrasonic loads compared to LED loads which exhibit higher voltage fluctuations. Thus, this tool can be an effective and environmentally friendly solution for shallot farmers in reducing pest attacks. By providing a performance analysis of different actuators under solar-powered constraints, this research contributes to the development of low-power, autonomous IoT system for smart agriculture.